Hydrogen addition for centimeter-sized monolayer tungsten disulfide continuous films by ambient pressure chemical vapor deposition - Sheng, Y; Tan, H; Wang, X; Warner, J (American Chemical Society, 2017)
Monolayer tungsten disulfide (WS 2 ) offers great prospects for use in optoelectronic devices due to its direct bandgap and high photoluminescence intensity. Here, we show how the controlled addition of hydrogen into the chemical vapor deposition growth of WS 2 can lead to the formation of centimeter scale continuous monolayer films at ambient pressure without the need for seed molecules, specially prepared substrates, or low pressure vacuum systems. Modifications of the reaction conditions, including growth time and hydrogen to argon ratio, allow for control over the domain size, film coverage, and film uniformity of the prepared WS 2 film. The combined control of hydrogen and a double-furnace system enables an increases in the growth rate of WS 2 , which results in fully merged films with cm 2 coverage and reduced multilayer content. Field effect transistors are fabricated to demonstrate that WS 2 has high quality for electronic applications. Our ambient pressure chemical vapor deposition reaction is simple and efficient, ideal for mass-production of large area monolayer WS 2 .